Analyzing the Influence of Digital Media on the Perceived Urgency of Neonatal Surgical Conditions Among Parents - Ahmed, Yasir; Singh, Jitendra; Bhardwaj, Ramiyan; Raza, Andleeb (Journal of Neonatal Surgery, 2025)
This study examines the impact of digital media exposure on parental perceptions of neonatal surgical conditions and decision-making behaviours. A sample of 168 parents from GMC Jammu Hospital and Sikims Hospital, Kashmir, completed a structured questionnaire assessing media consumption patterns and healthcare-related decisions. Pearson’s correlation coefficient was applied to analyze the relationships between digital media exposure, urgency perceptions, and decision-making behaviors. The results revealed a significant positive correlation between exposure to neonatal surgery-related media content and heightened perceptions of urgency (r = 0.992), as well as a strong influence of media frequency and content type (e.g., expert-driven and emotional content) on parental decision-making. These findings feature the critical role of digital media in shaping healthcare perceptions, highlighting the importance of expert-led, emotionally balanced content in neonatal health education.